2016
DOI: 10.1002/adem.201600219
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Microstructure and Hardening Behavior on Torsion Strain and Strain Rate in Extruded AZ31 Rods

Abstract: In this study, the effects of torsion strain and strain rate on microstructure and hardening behavior of extruded AZ31 Mg alloy rods are investigated. Torsion deformation can generate abundant extension twins and dislocations and cause the rotation of c‐axis toward extrusion direction. These microstructures exhibit gradient distributions along the radial direction of torsion‐deformed rods. Torsion deformation can effectively enhance the hardness of AZ31 rods. The gradient microstructure leads to a gradient har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The growing interest in energy conservation and emission reduction improves the utilisation of these lightweight alloys and then continues raising the requirements in understanding their mechanical properties [6][7][8][9]. Many reports studied the compression [8], tension [7,10,11], pre-deformation [1,12,13] and impact mechanical responses [8,14] of such materials. These contributions help a lot on constructing the constitutive model of Mg alloy which helpful to provide accurate predictions on stress-strain and forcedisplacement responses [7,15,16].…”
mentioning
confidence: 99%
“…The growing interest in energy conservation and emission reduction improves the utilisation of these lightweight alloys and then continues raising the requirements in understanding their mechanical properties [6][7][8][9]. Many reports studied the compression [8], tension [7,10,11], pre-deformation [1,12,13] and impact mechanical responses [8,14] of such materials. These contributions help a lot on constructing the constitutive model of Mg alloy which helpful to provide accurate predictions on stress-strain and forcedisplacement responses [7,15,16].…”
mentioning
confidence: 99%
“…The texture rotated in this study is identical to that reported in refs. [21,28]. Beausir et al [29] indicated that the ideal orientation of texture for extruded Mg alloys during torsion deformation is the B-fiber texture with the c-axis//ED.…”
Section: Microstructure Of the Free-end Torsion Samplementioning
confidence: 99%
“…In recent years, Guo et al [8,16] have pointed out that torsion processing is not only a common material fatigue test method, but an efficient strategy to prepare a quantitative controlled gradient structure for rod-shaped parts. High-performance gradient structural materials can be prepared by controlling torsion path [14,17], torsion speed [18], and the combined annealing process [19,20]. Recently, we have developed a new method to introduce a gradient of martensite phase in austenitic steels, with a volume fraction increasing from core to surface, via free-end torsion (FET).…”
Section: Introductionmentioning
confidence: 99%